Working with a diverse class: reflections on the role of team teaching, teaching tools and technological support - Wood, Lincoln; Reefke, H. (International Association for Development of the Information Society, 2010)
A variety of teaching methods and supportive tools are at a lecturer’s disposal. Comprehensive knowledge of such methods and tools and their effective use can enrich students’ lecture experiences and increase their ability as well as willingness to learn. Teaching in a team requires patience and time commitment from all staff involved but can prove to be a good approach to iteratively elevate the quality of course content as well as course delivery. Actively engaging students in a lecture environment and usage of methods that encourage class participation are additional facilitators that can yield a richer learning experience. Employing a pedagogical as well as an expert focus in combination is found to be a valid approach for continuous teaching improvement in a university environment. These insights are based on findings and experiences gained from several semester of teaching an introductory course to operations management in a team setting but may be regarded as partially generalisable and applicable to other teaching requirements.